Clinical analysis of hypophosphatemia induced by adefovir dipivoxil in treatment of chronic hepatitis B - YANG Xiaoyan (Linchuang Gandanbing Zazhi, 2015)
ObjectiveTo observe the occurrence of hypophosphatemia induced by adefovir dipivoxil (ADV) for the treatment of chronic hepatitis B and investigate the association between intact fibroblast growth factor 23 (iFGF23) and occurrence of hypophosphatemia, and to find a new way for early discovery and prevention of hypophosphatemic osteomalacia. MethodsA total of 1050 patients with chronic hepatitis B and hepatitis B cirrhosis who visited the First Affiliated Hospital of Zhengzhou University from December 2008 to December 2014 were analyzed retrospectively and divided into group A and group B according to different medications. The patients in group A (n=750) received ADV 10 mg/d and liver protection therapy, and those in group B (n=300) received entecavir (ETV) 500 mg/d and liver protection therapy, with a median treatment time of 76.652±5.053 months. The changes in the levels of serum phosphorus, iFGF23, alkaline phosphatase (ALP), and bone mineral density (BMD) during treatment were collected in the patients in both groups. Chi-square test was applied for comparison of categorical data between the two groups, and Spearman′s rank correlation was applied for correlation analysis. ResultsIn these 1050 patients, 47 patients experienced a persistent low level of serum phosphorus, consisting of 46 cases in group A (4 cases were diagnosed with hypophosphatemic osteomalacia) and 1 case in group B, and group A had a significantly higher incidence of hypophosphatemia than group B (6.13% vs 0.33%; χ2=16.859, P＜0.01). Group A also had significantly higher incidence rates of high iFGF23 and ALP levels and reduced BMD than group B (χ2=17.727, 10.823, and 13.578, respectively, all P＜0.01). The level of serum phosphorus was negatively correlated with that of iFGF23 (r=-0.906, P＜0.01), and was positively correlated with BMD (r=0.941, P＜001). ConclusionLong-term administration of ADV may cause hypophosphatemia, and high expression of iFGF23 may be related to the occurrence of hypophosphatemia. It is recommended that patients who take ADV for a long time be examined regularly for serum phosphorus, iFGF23, ALP, and BMD.